Empowering minds and fostering inclusion: ELT graduate students’ experiences with critical pedagogy - Zaimoğlu, Senem; Dağtaş, Aysun (Frontiers in Psychology, 2025)
IntroductionThis research focuses on how graduate students in a Master’s level English Language Teaching (ELT) program in Türkiye experienced transformative learning through a course on critical pedagogy (CP). Grounded in Mezirow’s transformative learning theory and Freirean principles, the study explores how engagement with the sociopolitical dimensions of language education challenged participants’ assumptions and transformed their cognitive, emotional, and relational understandings of teaching.MethodsData were collected from eight participants through weekly reflective journals structured around Gibbs’ Reflective Cycle that guides individuals to reflect systematically on their experiences and follow-up semistructured interviews. Following Braun and Clarke’s six-phase framework to thematic analysis, five overarching themes were identified that encapsulate the participants’ experiences: Confronting Disorienting Dilemmas, Shifting Perspectives (Cognitive Transformations), Navigating Emotional Journeys, Evolving Classroom Relationships, and Embracing Transformative Learning Processes.ResultsThe results revealed that participants encountered disorienting dilemmas that prompted self-examination and shifts in identity, beliefs, and pedagogical stances. While students valued dialogic learning, critical inquiry, and real-world connections, some reported discomfort when addressing controversial topics—highlighting persistent hierarchical dynamics within educational settings.DiscussionDespite these tensions, participants demonstrated growing commitment to inclusive and socially engaged teaching. This research contributes to inclusive teacher education by demonstrating how structured reflection and emotionally responsive learning environments can foster transformation. It also calls for further research on the long-term enactment of critical pedagogy in diverse institutional contexts.